Calvin and Canadian Protestantism: The Thought and Influence of W.W. Bryden - Vissers, John A. (Toronto journal of theology, 2015)
Walter W. Bryden (1883-1952), the sixth principal of Knox College (1945-1952), was arguably one of the most important Calvinist theologians in the history of Canadian Protestantism. In light of the 500th anniversary of John Calvin's birth (1509-1564) in 2009, this article explores Bryden's thought and influence as a Reformed Protestant theologian and Church leader in the Calvinist tradition and legacy that shaped Canadian Presbyterianism in the nineteenth and twentieth centuries. Bryden's own thinking about the significance of Calvin and Calvinism for the Presbyterian Church in Canada after Church union in 1925, especially in relation to the theology of Karl Barth, is explored in some detail. The Scottish theologian T.F. Torrance once remarked that Bryden was a truly remarkable theologian: "I can't help but think that he is more like John Calvin than anyone I've ever known." This article tests Torrance's impression by offering a critical examination of both the Calvinist tradition in Canada and Walter Bryden's interpretation of that tradition. The article argues that by the end of the nineteenth century there were three quite distinct (and competing) interpretations of Calvinist theology in Canada. By the 1930s Walter Bryden had forged a fourth trajectory in Reformed theology, one that became dominant in Canadian Presbyterianism and influential in other parts of Canadian Protestantism. The article concludes that there were, to be sure, many problems and limitations with Bryden's Calvinism. Nevertheless, Walter Bryden championed the essential insights of the Genevan Reformer and was able to leverage them in the Canadian context in ways that were important for the identity of post-union Canadian Presbyterianism.